Reading proficiency of CNHS Sophies basis for improving the English Tutorial Program - Wapille-Maghamil, Catalina B. (2009)
This descriptive type of research aims to determine the reading proficiency level of the CNHS second year students as well as their perception towards the English Tutorial Program of the LSU Languages Department. It was found out that the 63 respondents had moderately satisfactory reading proficiency level and that their perception level was positive. There is no significant relationship between their perception and proficiency level.
Keywords: Reading; Reading -- Ability testing